2018
DOI: 10.31234/osf.io/k4agy
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compliance with Ecological Momentary Assessment Protocols in Substance Users: a Meta-Analysis

Abstract: Introduction: Ecological Momentary Assessment (EMA) methods allow for real-time data collection in naturalistic environments, and are particularly informative for the examination of substance use which is both time and context dependent. Whilst there are considerable benefits to EMA, poor compliance to assessment protocols has been identified as a limitation, particularly in substance users. Little research has analysed factors which might influence compliance. Methods: The aim of this meta-analysis was to sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 1 publication
0
16
4
Order By: Relevance
“…Findings from this first study using EMA to understand day‐to‐day markers of depressive symptoms among cancer caregivers suggests that cancer caregivers are amenable to participating in studies with an EMA design and allays potential concerns that these designs may be too burdensome for this population. Although prompt completion rates in the present study did fall closely below the typical rates in prior EMA research, 27 , 28 engagement was not related to factors including caregivers' depressive symptoms, subjective caregiving burden, or the patients' care needs. Findings also support that caregivers' depressive symptoms relate in expected directions with their overall levels of self‐reported day‐to‐day negative and positive affect, although effects were not detected between caregivers' depressive symptoms and their affective variability.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Findings from this first study using EMA to understand day‐to‐day markers of depressive symptoms among cancer caregivers suggests that cancer caregivers are amenable to participating in studies with an EMA design and allays potential concerns that these designs may be too burdensome for this population. Although prompt completion rates in the present study did fall closely below the typical rates in prior EMA research, 27 , 28 engagement was not related to factors including caregivers' depressive symptoms, subjective caregiving burden, or the patients' care needs. Findings also support that caregivers' depressive symptoms relate in expected directions with their overall levels of self‐reported day‐to‐day negative and positive affect, although effects were not detected between caregivers' depressive symptoms and their affective variability.…”
Section: Discussioncontrasting
confidence: 78%
“…Our overall engagement of about 60% of prompts completed did not exceed our a priori benchmark of 65%, meaning our recorded engagement was slightly lower than average engagement typical in other EMA studies reported among the general population 27 28 Our engagement was also low compared to a previously published EMA study among cancer caregivers that recorded a 90.5% survey completion rate, though a key difference is that the previously published study examining communication and relationship satisfaction employed a design of twice‐daily prompts over 14 consecutive days 33 .…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Aggregated across the 5 recurring daily surveys (RDS), mean RDS compliance equaled 88.4%, and mean morning survey compliance equaled 81.9%. Both compliance rates exceed the pooled compliance rate shown in a recent meta-analysis on EMA and substance use (Jones et al, 2019). As a part of the parent study, all participants were trained on standardized drink equivalences set forth by the National Institute of Alcoholism and Alcohol Abuse (NIAAA; National Institute on Alcohol Abuse and Alcoholism, 2007).…”
Section: Daily Surveymentioning
confidence: 94%
“…Again, critical appraisal involves the systematic evaluation of study quality using a tool such as the Cochrane Collaboration's checklist (Higgins et al, 2011). Furthermore, only a handful (e.g., Jones et al, 2018;Woll & Schönbrodt, in press) have ever been pre-registered 4 , and there is no central collaboration akin to Cochrane, Campbell, or CEE in psychology. Taken together, the evidence suggests that although psychology and related social sciences make frequent use of meta-analyses, these meta-analyses are not often of the high methodological rigor required for the use of the label systematic review.…”
Section: Alternatives To and Supplements For Meta-analysismentioning
confidence: 99%